1995
DOI: 10.1021/ja00147a015
|View full text |Cite
|
Sign up to set email alerts
|

Transphosphorylation catalyzed by ribonuclease A: computational study using ab initio effective fragment potentials

Abstract: The transphosphorylation step in the enzyme-catalyzed hydrolysis of phosphate esters by Ribonuclease A (RNase A) is explored using ab initio quantum chemical methods. For the first time, components found in the RNase A active site are included in the all-electron chemical model, made up of 2-hydroxyethyl methyl phosphate monoanion used as the substrate, and small model compounds used to mimic the three important residues, His-12, His-119, and Lys-41, found in the RNase A active site. The remainder of the immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 0 publications
1
73
0
Order By: Relevance
“…27 This analysis is extended in Figure 4, which is a plot of logK p vs log(K m /k cat ). The shallow slope of this plot (near 0.2) indicates that Lys41 interacts far more extensively with the transition state than the product during catalysis of C>p hydrolysis.…”
Section: Is Uridine 2′3′-cyclic Vanadate a Transition State Analogue?mentioning
confidence: 98%
See 1 more Smart Citation
“…27 This analysis is extended in Figure 4, which is a plot of logK p vs log(K m /k cat ). The shallow slope of this plot (near 0.2) indicates that Lys41 interacts far more extensively with the transition state than the product during catalysis of C>p hydrolysis.…”
Section: Is Uridine 2′3′-cyclic Vanadate a Transition State Analogue?mentioning
confidence: 98%
“…[27][28][29] The Cys41 sulfhydryl group of K41C RNase A was modified by alkylation with bromoethylamine to yield a semisynthetic variant with an S-(aminoethyl)cysteine residue at position 41 (K41CEA RNase A) as described. 27 Uridine 3′-(p-nitrophenyl phosphate) [Up(OC 6 H 4 -p-NO 2 )] was synthesized by J. E. Thompson and T. G. Kutateladze as the 2′,5′-O-tetrahydropyranyl-protected material,30 and handled as described. 31 Sodium vanadate was obtained from Aldrich Chemical (Milwaukee, WI).…”
Section: Experimental Section Materialsmentioning
confidence: 99%
“…This then expels the 5′-hydroxyl group of the second nucleotide to cleave the P-O bond in a second step. We proposed this two-step phosphorane process to be the preferred path for the enzyme, a proposal further supported by computation (9)(10)(11). For a general review of phosphoranes as well-demonstrated intermediates in phosphate reactions, see ref.…”
mentioning
confidence: 88%
“…According to the generally accepted mechanism [1,27] His12 was unprotonated, and Lys41 and His119 were protonated. In addition, to evaluate our docking method, we also used the RNase A -cyclic uridyl phosphate (CUP) complex from previously published QM/MM calculations [28] to perform docking studies between CUP and the protein to reproduce this structure for verification.…”
Section: Protein Preparation In Silicomentioning
confidence: 99%